2015
DOI: 10.1016/j.ydbio.2014.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Nephron proximal tubule patterning and corpuscles of Stannius formation are regulated by the sim1a transcription factor and retinoic acid in zebrafish

Abstract: The mechanisms that establish nephron segments are poorly understood. The zebrafish embryonic kidney, or pronephros, is a simplified yet conserved genetic model to study this renal development process because its nephrons contain segments akin to other vertebrates, including the proximal convoluted and straight tubules (PCT, PST). The zebrafish pronephros is also associated with the corpuscles of Stannius (CS), endocrine glands that regulate calcium and phosphate homeostasis, but whose ontogeny from renal prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 81 publications
(149 reference statements)
3
82
0
Order By: Relevance
“…Modulating levels of RA affects the specification of renal progenitors, inducing proximal segment lineage formation over distal, which can be accentuated by the addition of exogenous all-trans RA, while distal fates are induced over proximal by inhibiting endogenous production of RA through the application of the biosynthesis inhibitor N,N-diethlyaminobenzaldehyde (DEAB) (Wingert et al, 2007; Wingert and Davidson, 2011). Through expression profiling and subsequent functional studies, several transcription factors have been mapped as acting downstream of RA signaling to regulate pronephros segmentation and epithelial fate choice, including hepatocyte nuclear factor-1 beta (paralogues hnf1ba and hnf1bb ), iroquois homeobox 3b ( irx3b ), mds1/evi1 complex ( mecom ), single minded family bHLH transcription factor 1a ( sim1a ), and t-box 2 (paralogues tbx2a and tbx2b ), among others (Wingert and Davidson, 2011; Naylor et al, 2013; Li et al, 2014; Kroeger and Wingert, 2014; Cheng and Wingert, 2015; Marra and Wingert, 2016Marra et al, 2016; Drummond et al, 2017). Despite these advances, the identity of the other essential signals that control renal progenitor fate decisions has remained elusive (Cheng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Modulating levels of RA affects the specification of renal progenitors, inducing proximal segment lineage formation over distal, which can be accentuated by the addition of exogenous all-trans RA, while distal fates are induced over proximal by inhibiting endogenous production of RA through the application of the biosynthesis inhibitor N,N-diethlyaminobenzaldehyde (DEAB) (Wingert et al, 2007; Wingert and Davidson, 2011). Through expression profiling and subsequent functional studies, several transcription factors have been mapped as acting downstream of RA signaling to regulate pronephros segmentation and epithelial fate choice, including hepatocyte nuclear factor-1 beta (paralogues hnf1ba and hnf1bb ), iroquois homeobox 3b ( irx3b ), mds1/evi1 complex ( mecom ), single minded family bHLH transcription factor 1a ( sim1a ), and t-box 2 (paralogues tbx2a and tbx2b ), among others (Wingert and Davidson, 2011; Naylor et al, 2013; Li et al, 2014; Kroeger and Wingert, 2014; Cheng and Wingert, 2015; Marra and Wingert, 2016Marra et al, 2016; Drummond et al, 2017). Despite these advances, the identity of the other essential signals that control renal progenitor fate decisions has remained elusive (Cheng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish development occurs ex utero and with minor pigmentation, allowing for direct observation of renal organogenesis and monitoring of responses to external cues 34 . Tools for molecular analysis, such as gene expression 3537 , have been utilized with high resolution to determine the features of nephrogenesis 3840 . Experimental manipulations for testing of small molecules through chemical genetics are well established in zebrafish and applicable to the kidney 4143 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite these differences, it has been shown that the segment pattern in the nephrons of the zebrafish pronephros [61] and mesonephros [62][63][64] is remarkably similar to the segment pattern in nephrons of other vertebrates, supporting the notion that nephron composition is the evolutionary link across species with diverse forms that inhabit a wide range of environments [60] . This has spurred a number of segmentation studies utilizing the zebrafish pronephros [65][66][67][68][69][70] , which further suggest nephrogenesis mechanisms have been conserved during evolution [60] . The zebrafish pronephros and mesonephros are therefore useful for studying developmental and regenerative pathways.…”
Section: The Zebrafish: a Model For Kidney Researchmentioning
confidence: 99%